Land Commodification and Housing Affordability under Capitalist Urbanisation. Global dynamics and local resistance in Peru, the United Kingdom and the United States - (:unkn) unknown (My University, 2026)
This initiative facilitates a global North-South exchange of ideas to enrich the debate on how the commodification of land under intensifying capitalist accumulation generates complex urbanisation dynamics in different regions, particularly vis-à-vis the